Uma nova abordagem analítica sobre teores de 'Zn' por HR-CSAAS em plantas medicinais voltadas ao emagrecimento - Ishikawa, Fabio Genhiro [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The following research project deals with the development of new analytical procedures aimed at the identification and quantification of the element zinc in different fractions of vegetable drugs used for weight loss, using the high-resolution continuum source atomic absorption spectrometry in flame. The determination of the levels of zinc was made in an AnalytikJena ContrAA 300 spectrometer in the principal line of Zn at 213.857 nm and wavelength integrated absorbance equal to 3 pixels. Calibration curves were obtained with linear dynamic range from 0.10 to 1.00 mg L-1, correlation coefficient equal to 0.9991 and limit of detection equal to 0.020 mg L-1. The total Zn content in the samples obtained after microwave-assisted acid digestion system were: 28.06 mg kg-1 (Artichoke), 31.49 mg kg-1 (Chamomile), 77.16 mg kg-1 (Gorse), 105.38 mg kg-1 (Horsetail), 32.37 mg kg-1 (Fennel) and 5.00 mg kg-1 (Senna). The extraction in aqueous environment assisted by microwave radiation produced extracts containing: 5.40 mg kg-1 (Artichoke), 10.65 mg kg-1 (Chamomile), 14.83 mg kg-1 (Gorse), 18.90 mg kg-1 (Horsetail), 7.80 mg kg-1 (Fennel), 3.24 mg kg-1 (Senna), corresponding to 19%, 34%, 19%, 18%, 24% and 64% of their total content of Zn, respectively. The amounts of Zn in the extracted samples from some plants indicate that this metal was strongly bounded to the plant's matrix. The sequential extraction using solvents and mixtures with different polarities (n-hexane, ethyl acetate, propanol, methanol, ethanol-water 1:1 (v/v), water) aimed the separation of different Zn containing species and water was considered the most efficient extractor. The Zn contents extracted were: 14.82 mg kg-1 (Artichoke), 16.82 mg kg-1 (Chamomile), 34.09 mg kg-1 (Gorse), 4.75 mg kg-1 (Senna), corresponding to 53% in the first two samples, 44% and 95% for the last two, respectively. It was observed that Zn is found complexed under
Keywords: Medicinal plants; Sequential extraction; Plantas medicinais; Espectrometria de absorção atômica; Extração sequencial; Zinco